TENAGA KERJA INDONESIA DALAM KONTEKS MASYARAKAT TAIWAN YANG MENUA - Rita Pawestri Setyaningsih (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2016)
Taiwan’s ageing population has boosted the high rate of demand for caretakers. Many caretakers came from Southeast Asian countries such as the Philippines, Vietnam, Thailand, and Indonesia. Since 2005 Indonesian Workers have dominated the market share of the welfare sector. However in 2015 the Indonesian government launched a zero-maid policy, in order to terminate the sending of unskilled workers. The other goal is to provide better protection for migrant workers abroad. Taiwan becomes one of the targets of this policy. In fact, this policy will certainly create great impact on the supply of labor in the welfare sector in the future. Moreover, Taiwan has launched a national ten-year long-term care. So, how the Taiwanese government respond to this policy? Will the Indonesian workers’ shalt position be replaced by other Southeast Asian workers? This article aims firstly, to understand the position of migrant workers among other foreign workers working in the welfare sector in Taiwan. Secondly, to understand the Taiwan government’s efforts in response to the Indonesian government’s plan. This study uses literature study and interviews. This issue will be analyzed using economic and social approaches. The data used are from the range of 1992 to 2015.Keywords: ageing society, Taiwan, Indonesian workers, employment policyAbstrakPenuaan penduduk Taiwan mendorong tingginya laju permintaan akan tenaga perawat. Selama ini tenaga perawat didatangkan dari negara-negara Asia Tenggara, seperti Filipina, Vietnam, Thailand, dan Indonesia. Sejak 2005 Tenaga Kerja Indonesia (TKI) mendominasi pangsa pasar sektor kesejahteraan sosial. Namun di tahun 2015, Pemerintah Indonesia mencanangkan zero-maid policy, yaitu penghentian pengiriman TKI tidak terampil. Tujuannya tidak lain adalah untuk memberikan perlindungan yang lebih besar bagi TKI di luar negeri. Taiwan menjadi salah satu target dari kebijakan ini. Kebijakan ini tentu akan berdampak pada ketersediaan tenaga kerja pada sektor kesejahteraan sosial di Taiwan di masa depan. Apalagi Taiwan sudah mencanangkan national ten-year long-term care. Lantas, bagaimana respon pemerintah Taiwan terhadap kebijakan ini? akanlah TKI digantikan posisinya oleh TKA lainnya? Artikel ini bertujuan untuk pertama, memahami posisi TKI di antara tenaga kerja asing lainnya yang bekerja di sektor informal di Taiwan. Kedua, memahami upaya pemerintah Taiwan dalam menanggapi rencana pemerintah Indonesia tersebut. Studi ini menggunakan studi literatur dan wawancara. Persoalan ini akan dianalisis dengan menggunakan pendekatan ekonomi dan sosial. Data yang digunakan adalah data sekunder dari tahun 1992 hingga 2015.Kata kunci: ageing society, Taiwan, TKI, kebijakan ketenagakerjaan